Empirical classification and effect of procurement process on organisational performance outcomes. (2019) - Harb, Atef; Antoun, Reine Abou; Kassem, Abdallah; Baena, César
For many years, purchasing and procurement became a major concern for researchers and decision makers worldwide. In Lebanon, the purchasing functions have become recently a major concern for different organisations and industries. So, the purpose of this research is to investigate the different purchasing clusters of Lebanese industrial and engineering organisations and to study their effect on organisational management and performance. Two research questions addressed and two hypotheses tested using 95 Lebanese organisations. Findings supported the two hypotheses and showed statistically a significant relation between the two studied variables. As a conclusion, this research assessed, analysed and presented the importance of purchasing clusters and its positive influence on organisational performance in the Lebanese organisations/industries. The findings will be very useful for decision makers, engineers, researchers and practitioners seeking to improve the performance and standing of the purchasing function through the identification of the different characteristics and potential limitations faced at each phase.